A new region-aware bias-correction method for simulated precipitation in areas of complex orography - J. J. Gómez-Navarro; J. J. Gómez-Navarro; J. J. Gómez-Navarro; J. J. Gómez-Navarro; C. C. Raible; C. C. Raible; C. C. Raible; D. Bozhinova; D. Bozhinova; O. Martius; O. Martius; O. Martius; et al. (Geoscientific Model Development, 2018)
Regional climate modelling is used to simulate the hydrological cycle, which is fundamental for climate impact investigations. However, the output of these models is affected by biases that hamper its direct use in impact modelling. Here, we present two high-resolution (2 km) climate simulations of precipitation in the Alpine region, evaluate their performance over Switzerland and develop a new bias-correction technique for precipitation suitable for complex topography. The latter is based on quantile mapping, which is applied separately across a number of non-overlapping regions defined through cluster analysis. This technique allows removing prominent biases while it aims at minimising the disturbances to the physical consistency inherent in all statistical corrections of simulated data.